2004
DOI: 10.1085/jgp.200409040
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II (AT1) Receptors and NADPH Oxidase Regulate Cl− Current Elicited by β1 Integrin Stretch in Rabbit Ventricular Myocytes

Abstract: Direct stretch of β1 integrin activates an outwardly rectifying, tamoxifen-sensitive Cl− current (Cl− SAC) via focal adhesion kinase (FAK) and/or Src. The characteristics of Cl− SAC resemble those of the volume-sensitive Cl− current, ICl,swell. Because myocyte stretch releases angiotensin II (AngII), which binds AT1 receptors (AT1R) and stimulates FAK and Src in an autocrine-paracrine loop, we tested whether AT1R and their downstream signaling cascade participate in mechanotransduction. Paramagnetic beads coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 83 publications
(136 reference statements)
7
107
0
Order By: Relevance
“…20,28 In addition, signaling pathways contributing to VRAC activity include phosphatidyl-inositol-3-phosphate kinase (PI3K), NADH-dependent oxidases and reactive oxygen species (ROS) as well as tyrosine kinases. [29][30][31][32][33][34][35][36] Recently it was demonstrated that knockdown of integrin b 1 reduces RVD in adherent Ehrlich Lettre ascites cells (ELA) cells 37 and as integrin b 1 stretch in Figure 1. VRAC characteristics.…”
Section: Biophysical Characterization Of Vracmentioning
confidence: 99%
See 1 more Smart Citation
“…20,28 In addition, signaling pathways contributing to VRAC activity include phosphatidyl-inositol-3-phosphate kinase (PI3K), NADH-dependent oxidases and reactive oxygen species (ROS) as well as tyrosine kinases. [29][30][31][32][33][34][35][36] Recently it was demonstrated that knockdown of integrin b 1 reduces RVD in adherent Ehrlich Lettre ascites cells (ELA) cells 37 and as integrin b 1 stretch in Figure 1. VRAC characteristics.…”
Section: Biophysical Characterization Of Vracmentioning
confidence: 99%
“…9D), (iv) sensitivity to membrane potential (VSOAC inhibited by depolarization / VRAC shows outward rectification and varying degree of inactivation at positive potentials 7 ), and (v) regulation via integrin b 1 , i.e., VSOAC is unaffected by integrin b 1 knockdown 37 whereas VRAC is activated by integrin b 1 stretch. 34,38,92 Variation in stoichiometry of LRRC8 components and their regulation / localization to subdomain in the plasma membrane could explain differences between VSOAC and VRAC activities (see below).…”
Section: Volume-sensitive Organic Anion Transporters -Vsoacmentioning
confidence: 99%
“…A study of the effects of Ang II in adult rats showed myocyte hypertrophy and midmyocardial interstitial fibrosis (Grobe et al, 2007). Ang II mediated cardiac remodeling is facilitated through myocardial AT 1 receptors and subsequent intracellular signaling (Browe & Baumgarten, 2004;de Gasparo et al, 2000).…”
Section: Angiotensin IImentioning
confidence: 99%
“…Wright et al [92] showed that prolyl hydroxylation is the oxygen-sensing mechanism in cardiac myocytes, which in turn regulates HIF-1, heme oxygenase-1, and GLUT1. While the role of NADPH oxidase in O 2 sensing in cardiac myocytes has not been reported, this enzyme has been shown to be expressed and play a role in the development of cardiac hypertrophy and in the transition to heart failure [93][94][95][96][97][98][99][100]. The concept that the heart directly senses changes in oxygen tension has recently been supported by results from our laboratory that 20 min of intermittent hypoxia can elicit significant changes in gene expression and protein modifications in mouse hearts [101].…”
Section: Oxidative Stress In Animal Models Of Intermittent Hypoxiamentioning
confidence: 99%